Strength and Poisson’s ratio of fused filament fabrication parts made from carbon filler enhanced PEEK compounds at elevated temperatures - Leo Nyman; Pauli Lehto; Kirsi Kukko; Antti Kestilä; Esa Kallio (Scientific Reports)
Abstract Engineering plastics are finding widespread applications across a broad temperature spectrum, with additive manufacturing (AM) having now become commonplace for producing aerospace-grade components from polymers. However, there is limited data available on the behavior of plastic AM parts exposed to elevated temperatures. This study focuses on investigating the tensile strength, tensile modulus and Poisson’s ratio of parts manufactured using fused filament fabrication (FFF) and polyetheretherketone (PEEK) plastics doped with two additives: short carbon fibers (SCFs) and multi-wall carbon nanotubes (MWCNTs). Tensile test specimens, conforming to the ISO 527 type-1b standard and printed in the XY-plane, were subjected to elevated temperatures (110 °C, 130 °C). After temperature stabilization, a tensile test was conducted to evaluate how elevated temperatures affect the mechanical properties of the parts. The results were compared to tensile test results obtained at room temperature. Additionally, computed micro-tomography was used to determine the porosity of the FFF parts. Furthermore, differential scanning calorimetry measurements were made. The results indicate that exposure to the elevated temperature range used in this work can reduce the tensile strength by 36%. The effects on the tensile modulus and Poisson’s ratio were less pronounced. Based on these findings, SCF-PEEK FFF parts demonstrate higher tensile modulus and specific strength compared to plain-PEEK at elevated temperatures (110–130 °C), supporting their use in lightweight aerospace structures.